Cow felling depending on the state of exchange of substances in the synchronization of estrus - Краєвський, А. Й.; Лазоренко, А. Б.; Травецький, М. О.; Краєвський, С. А.; Галічев, М. М. (Scientific Progress & Innovations, 2017)
The article presents the results of studies on the fertilization of cows, depending on the state of metabolism before the synchronization of estrus. It was found that a decrease in the content of total protein, calcium, inorganic phosphorus and carotene in the serum, together with the development of compensated acidosis, significantly reduces the level of fertilization of cows.